A NEW SPECIES OF CASTILLEJA (OROBANCHACEAE) FROM THE PÁRAMOS OF THE COLOMBIAN EASTERN CORDILLERA, WITH COMMENTS ON ITS ASSOCIATION WITH PLANTAGO RIGIDA (PLANTAGINACEAE) - FAVIO GONZÁLEZ; NATALIA PABÓN-MORA (Caldasia)
Castilleja paramensis F. González & Pabón-Mora, a perennial species of small herbs from páramos of Santander, Boyacá and Cundinamarca, in the Colombian Eastern Cordillera, is described and fully illustrated by photographs of the type collection. The new species is morphologically and ecologically similar to C. nubigena, C. pumila, and C. virgata, three perennial high Andean species from Ecuador, Peru and northern Chile and Argentina. C. paramensis is clearly distinguished from its relatives by the small size of the individuals, the broadly elliptic leaves and bracts (which are entire to slightly trilobed), the short (< 1 mm ) pedicel, the small size (0.8- 1.15 cm long) of the flowers, the not inflated calyx with the distal half bright yellow, the corolla often included to slightly exserted from the calyx, and the included style and stigma. The included corolla, stamens, styles and stigmas in C. paramensis strongly suggest the occurrence of cleistogamy. The new species often grows as a root hemiparasite of Plantago rigida.